PENERAPAN STRATEGI THINK TALK WRITE (TTW) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMP AN NAMIROH PEKANBARU - Dian Rifia Syaifudin; Armis '; Zuhri ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to improve the learning process and increase the student’s learning outcomes through the implementation of Think Talk Write (TTW) Strategy. The research is the Classroom Action Research with two cycles. The research was conducted in student of grade VII of Junior High School An Namiroh Pekanbaru in the second semester of the 2015/2016 academic year with the subject are 32 students. The research instrument are consists of learning devices and instrument data collectors. Learning devices used in this research are consists of the Syllabus, Lesson plan and Student work sheet. The instrument data collector used in this research is consists of the observation sheet and math test. Technique of data analysis is analysis of narrative descriptive and analysis of statistical descriptive. Based on the result of the research show that, the learning process has improved looks on implementation of learning is getting better for each meeting and the student’s learning outcomes have increased looks on increasing the number of students who achieve of KKM on daily test I and daily test II compared to the base score after applying the Think Talk Write (TTW) Strategy. The Think Talk Write (TTW) Strategy can be used as an alternative in learning, because it can improve the learning process and increase the student’s learning outcomes.                                                                                                                         Key Words: Think Talk Write (TTW) Strategy, student’s learning outcomes